Comparing the effects of an aerobic exercise program and group-based play therapy on the balance of children with Attention Deficit Hyperactive Disorder (ADHD) - Elham Bakhshipour; Nader Rahnama; Hossein Sourtiji; Zahra Skandari; Sara Izadi Najafabadi (Vesnu Publications, 2013)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder usually characterized by poor coordination and clumsiness. It seems that rhythmic aerobic exercise has the same effect on affected children's balance as play therapy. The aim of this study was to compare the effect of an aerobic exercise program with that of group play therapy on the balance abilities of children with ADHD. Materials and Methods: In this study, 26 children with attention deficit hyperactivity disorder (4 girls and 22 boys) were assigned to 2 experimental groups (group-based play therapy and aerobic exercise groups) and one control group. Each experimental group received its respective intervention program 3 sessions a week, lasting 45 to 60 minutes each, over an 8-week period. Results: Significant differences were observed between group-based play therapy group and aerobic group regarding dynamic balance. There was, however, no significant difference between experimental groups as long as static balance was concerned. Conclusion: Although group-based play therapy had greater impact on improving the balance of children with ADHD, aerobic exercise program had significant effects on improving static balance. Therefore adding aerobic exercise to routine group play therapy may bring more benefits to children with ADHD. Keywords: ADHD, Aerobic exercise, Play therapy, Balance